Estimation of speed-sensitive thermal model for dc machines using transfer function - Muhammad Syawal, Mat Jahak (2025)
Motors account for 40% of global electricity consumption and 13% of carbon emissions and often suffer irreversible thermal damage. To prevent excessive electrical waste and improve reliability, it’s crucial to monitor motor temperature accurately and halt operation at safe levels. This study aims to develop a real-time model for monitoring motor temperature in MY1016 direct current machines, using a transfer function. The objectives include identifying the most precise transfer function to model the temperature response of each component at different speed, developing, and validating a generalized model using averaged-pole and variable-pole transfer function models, and finally evaluating their feasibility for fault detection. Experimental data was recorded for different motor components including the brush, bearing, permanent magnet and casing. The motor was operated at speeds from 20% to 100% of nominal speed with no load, until thermal equilibrium was reached. The MATLAB system identification toolbox was used to identify the transfer function, with a number of poles varying from 1 to 4 and with no zeros. The study found that the temperature response of the MY1016 motor at 60% of the nominal speed produces the highest temperature. The brush was best represented by a 3rd order transfer function, while a 1st order transfer function is sufficient to represent other components. The non-LTI characteristic of the temperature response observed from the pole analysis led to a choice of modeling using variable-pole transfer function to create the baseline temperature model. It can estimate temperature response during both steady and transient speed states, with a maximum temperature difference of 10 ℃. The study concludes that the variable-pole transfer function can be used to monitor electric motors' condition using several testing scenarios. The same method can be suggested to be applied on other types of motors.